Moments of inertia in light deformed nuclei: Pairing and mean-field impacts - Nesterenko, V. O.; Mardyban, M. A.; Reinhard, Paul-Gerhard; Repko, A.; Kvasil, J. (International Journal of Modern Physics E-Nuclear Physics, 2024)
The dependence of the moment of inertia on the pairing and axial quadrupole deformation β in 24Mg and 20Ne was investigated. The study is based on quadrupole-constrained calculations with three cranking approaches for (Inglis-Belyaev, Thouless-Valatin, adiabatic time-dependent Hartree-Fock) and a representative set of Skyrme forces (SVbas, SkM*, SLy6). At variance with macroscopic collective models, the calculations predict the specific regime djdβ<0 at β≥0.5 (24Mg) and β≥0.6 (20Ne), where the pairing breaks down. This regime is explained by two effects: full break up of the pairing and specific evolution of a single dominant particle-hole (1ph) configuration with β. The analysis of experimental data for the ground-state rotational bands in 24Mg and 20Ne shows that such regime is possible at low spins.
CRIS-Team Scopus Importer:2025-02-04
Keywords: deformation and pairing; Light deformed nuclei; moments of inertia; random-phase approximation; single-particle levels; Skyrme density functional theory